Electronic Customer Relationship (e-CRM): a pulse on the retailing community / Engku Badrul Nizam Engku Abdul Rahman - Engku Abdul Rahman, Engku Badrul Nizam (2005)
e-CRM is an Electronic Customer Relations Management solution, specifically designed and developed to suit all front and back office needs. e-CRM will assist in maintaining and organizing all sales leads, customer base information, list of products, quotation generating and tracking and competitor analysis. With eCRM, organizations can have instant access to up-to-date information and all the latest on-goings of the organization, at anytime and anywhere. This system is made to facilitate retaining existing customers, and also broadens organization's prospects in the current challenging global market. It is fully equipped with the latest technology to vastly enhance organizations' competitive advantage, while maximizing overall operational efficiency and substantially reducing unnecessary overhead costs. e-CRM enables organizations to foster a more fruitful relationship with their customer, while simultaneously monitoring and boost customers' satisfaction of the products and services. This research will investigate the implementation of e-CRM by the main retailing sector in Malaysia, focusing on area of Klang valley. The issues such as the way of implementation, risks, risks management and customers feedback will be discusses by the researcher. The recommendation about the implementation also included upon this research.